Relationships between silage fermentation characteristics and milk production parameters : analyses of literature data - Huhtanen, Pekka; Nousiainen, Jouni I; Khalili, Hannele; Jaakkola, Seija; Heikkilä, Terttu (Elsevier, 2003)
Data from published production studies in lactating dairy cows were used to estimate relationships between silage fermentation characteristics and milk production parameters. The study used data from 47 experiments including 234 observations (treatment means). Within each experiment the silages were harvested at the same time from the same sward but using various additives. When factorial designs were used, silage data within each treatment (subexperiment) were recorded separately. Relationships between production parameters and silage fermentation parameters were analysed using mixed model regression analyses; with subexperiment within experiment as a random factor. Yields of milk, energy corrected milk (ECM), milk fat and protein decreased with increasing extent of in-silo fermentation. The effects were more profound for ECM than milk yield, because both milk fat and protein concentrations decreased (P<0.001) with increasing silage lactic acid or total acid concentrations. In most cases total acid concentration was the best single predictor of production parameters, although multiple regression equations generally explained the variation better than single regressions. Yield of ECM decreased by 18.9, 25.4 and 19.1 g per g/kg DM increase in the concentration of lactic acid, volatile fatty acids (VFA) or 1 g/kg N increase in ammonia N concentration. Multiple regression analyses also showed a greater negative effect of VFA compared to lactic acid on the yields of ECM, milk fat and protein. The best multiple equations explained between 0.25 and 0.35 of the variation in ECM, milk fat or protein yield within experiment. The effects of extent of fermentation and ammonia N on production parameters were additive. Reduced milk fat content with increasing extent of in-silo fermentation appears to be related to reduced proportion of lipogenic VFA in the rumen. Lower milk protein content for extensively fermented silages can be attributed to reduced silage DM intake and microbial protein synthesis in the rumen. Proportional decreases in the yield of milk components with increasing extent of in-silo fermentation were the smallest for lactose and the highest for milk fat. Yield of ECM increased by 0.12 kg/MJ additional metabolizable energy (ME) in response to increased DM intake with improved fermentation quality. In studies conducted in Finland the within-experiment R2 value between ME intake and ECM yield was 0.74 indicating that the effects on ECM yield were mainly derived from increased silage intake.
Keywords: Ko; lypsykarja; lehmät; märehtijät; ruokinta; ravinnonsaanti; rehut; säilörehu; käyminen; maidontuotanto; dairy cattle; dairy cows; feeding; nutrient intake; feeds; silage; fermentation; milk production; grass silage; fermentation parameters; nutrient supply